THE ORETICAL ASPECTS OF DEVELOPING BIOETHICAL CULTURE OF BIOLOGY STUDENTS (Scientific journal of the Fergana State University, 2026)
The article analyzes the theoretical and methodological foundations for developing bioethical culture among students majoring in biology. Special emphasis is placed on the pedagogical system aimed at fostering bioethical awareness through interdisciplinary cooperation and evaluating its effectiveness. Both theoretical approaches and practical mechanisms for instilling bioethical values in biology students are discussed.